2013
DOI: 10.1371/journal.pone.0053483
|View full text |Cite|
|
Sign up to set email alerts
|

Genotypes and Mouse Virulence of Toxoplasma gondii Isolates from Animals and Humans in China

Abstract: BackgroundRecent population structure studies of T. gondii revealed that a few major clonal lineages predominated in different geographical regions. T. gondii in South America is genetically and biologically divergent, whereas this parasite is remarkably clonal in North America and Europe with a few major lineages including Types I, II and III. Information on genotypes and mouse virulence of T. gondii isolates from China is scarce and insufficient to investigate its population structure, evolution, and transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 47 publications
6
104
0
2
Order By: Relevance
“…There are three forms of T. gondii, they are tachyzoite (proliferative forms), cysts (containing bradizoit), and oocysts (containing sporozoite) [1] [2] [3] [4]. T. gondii consists of three types (type I, II and III) and two types from recombination (types IV and V) and has a different pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three forms of T. gondii, they are tachyzoite (proliferative forms), cysts (containing bradizoit), and oocysts (containing sporozoite) [1] [2] [3] [4]. T. gondii consists of three types (type I, II and III) and two types from recombination (types IV and V) and has a different pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are at least more than 120 genetic markers that have been developed and used for the determination of T gondii type [5] [6]. Toxoplasmosis is a zoonotic disease caused by T. gondii [4]. Toxplasmosis is an important zoonotic disease caused by protozoan parasite T. gondii.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data are necessary to define preventive, management, and therapeutical measures for stray, feral, and domestic cats. Although several studies have reported the T. gondii prevalence in cats in various regions in China (Dubey et al 2007;Chen et al 2011;Qian et al 2012;Wang et al 2013;Tian et al 2014), including Lanzhou (Wu et al 2011), little is known of the genotypes of T. gondii in cats in northwest China. Here, we investigated the genotypes of T. gondii in cats in northwest China for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…La variación genética entre estos linajes es entre 1 y 3%, y la variación dentro de un linaje es muy baja (< 0,01) 40 . Las cepas con combinaciones atípicas se han aislado en presentaciones clínicas inusuales en humanos 41 , principalmente en Sudamérica (SA) 37 y en Asia 43 . Son desconocidas las causas por la cual estas cepas se encuentran confinadas sólo en ciertas zonas geográficas (SA).…”
Section: Genotipificación De Toxoplasma Gondiiunclassified